Model Rapid Application Development Dalam Perancangan Aplikasi Reservasi Hotel Dengan Konsep Pemrograman Terstruktur - Ida Darwati; Retno Sari (JURNAL TEKNIK KOMPUTER AMIK BSI, 2019)
Nowadays promotions and transactions via the internet are not uncommon, many companies have used the internet as a medium of promotion and even transactions online, because using a website is believed to be able to expand the area of promotions and transactions that do not know the time and place. The wider the range of promotions, the greater the chance of a transaction, which can be done from anywhere and at any time with the condition of being connected to the internet network, so as to provide convenience for both the customer and the company. Likewise with hotels that already use internet facilities, it can make it easier for customers to know what types of rooms are available and can make reservations online. In addition, customers can look at room types and find out information about room facilities offered. The author uses the RAD model to design a web-based hotel reservation program.